KERAGAMAN JENIS JAMUR ENDOFIT PADA PANDAN WANGI (PANDANUS AMARYLIFOLIUS) DAN AKTIVITAS ANTIJAMUR METABOLIT YANG DIPRODUKSINYA - Jamal, Yuliasri; Ilyas, Muhamad; Kanti, Atit; Agusta, Andria (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2009)
The whole nine isolates of endophytic fungi have been obtained from leaves and roots of pandan wangi (Pandanus amarylifolius) collected from Bogor Botanical Garden. Identification of the fungi isolates were conducted based on their morphological characteristics, and revealed that one fungus belongs to the genus of Fusarium, one of Dreschlera, and 7 fungi isolates belong to Coelomycetes. The ethyl acetate extract of the fungi cultures in PDB and GYP media showed a diverse secondary metabolite profiles. Ethyl acetate extract derived from the culture of PWA-2 fungus in GYP medium showed an antifungal activity against Saccharomyces cerevisiae, but not to Fusarium oxysporum and Candida tropicalis. The GC-MS analysis of the active extract showed eugenol as an active component.